Persistent Inflammation in Pulmonary Granuloma 48 Years after Talcage Pleurodesis, Detected by FDG-PET/CT - J. C. Fanggiday; R. W. Rouse; S. M. Collard; M. J. de Haas; J. M. H. de Klerk (Case Reports in Medicine)
In patients with suspicion of lung malignancy, FDG PET/CT is frequently used as a diagnostic and staging imaging modality. However, false positive findings are not uncommon. We demonstrate a case with FDG-avid pulmonary nodules, mimicking lung cancer. After histopathological examination they appeared to be the result of persistent inflamed tissue, due to talcage pleurodesis, which occurred 48 years ago. We concluded that, nearly five decades after talcage pleurodesis, there can still be an ongoing inflammation reaction in the pleurae, which can be detected by FDG PET/CT.